Intimate Empire : Collaboration and Colonial Modernity in Korea and Japan - Kwon, Nayoung Aimee (Book collections on Project MUSE., 2015)
Nayoung Aimee Kwon examines the Japanese language literature written by Koreans during late Japanese colonialism. She demonstrates that simply characterizing that literature as collaborationist obscures the complicated relationship these authors had with colonialism, modernity, and identity, as well as the relationship between colonizers and the colonized